Phenotypic change in neutrophils in patients with Acne Vulgaris (Texas Journal of Medical Science, 2021)
The widespread prevalence, material and moral damage, a tendency to chronicity and frequent recurrence, lack of effectiveness of therapy determine the relevance of the studied problem